Recurrent Stroke In 34 Year-Old, Unusual Presentation of Non-Bacterial Endocarditis - Y, Zhang; KW, Klarich; S, Cicek; J, Maleszewski; AI, Casanegra (Archives of Clinical and Medical Case Reports, 2020)
Factor V Leiden (FVL) and prothrombin G20210A (PGM) mutations are the most frequent genetic risk factors involved in deep venous thrombosis in Caucasians. Being heterozygous for both seems to increase the risk of venous events but it is not well established if the association increases the risk of arterial thrombosis or other thrombotic events. We present a case of recurrent stroke caused by non-bacterial thrombotic endocarditis (NBTE) in a 34-year-old Caucasian man heterozygous for both FVL and PGM. His diagnosis of NBTE was confirmed with pathology in the absence of other causes of NBTE.